Burden of non-communicable diseases and its associated economic costs in India. Issue 1 (2022) - Menon, Geetha R.; Yadav, Jeetendra; John, Denny
Abstract: Background: Non communicable diseases (NCD) are a rising problem worldwide and is a cause of public health concern in India too. These diseases result in high health care demand and are expensive especially in low resource settings. We studied the NCD burden estimates for India and its major states and the associated cost in 2017. Methods: The disease burden was estimated using DALYs (Disability Adjusted life years), the Years of Life lost (YLL) and Years lived in disability (YLD). Health expenditure data from National Sample Survey was used to calculate out of pocket expenditure (OOPE) and catastrophic health expenditure (CHE). Results: NCDs account for 16939 DALYs per 100 000 in India. About 50–70% of patients took treatment in private facilities. There is huge variation in the utilization of health facilities, disease burden and cost of treatment across the states. Karnataka had highest DALY rate of 25790 DALYs per 100 000 but Chandigarh showed highest mean OOPE of INR 63952 and Arunachal Pradesh showed the highest CHE of 47.7 percent. Conclusions: The economic burden of NCDs is notably high both in terms of OOPE and CHE and indicate variation across states in both disease burden and economic burden. The findings highlight the need for improvement of NCD management programmes in socioeconomically lower states of India.